A new candidate for antitheilerial target: isolation, cloning and sequence analysis of gene encoding the enolase enzyme from Theileria parva - Celik, V.; Icen, I.; Pelle, R.; Kurt, A. G.; Munzuroglu, O.; Geckil, H. (Wiley-Blackwell, 2011)
[Abstract Not Available]
36th FEBS Congress of the Biochemistry for Tomorrows Medicine -- JUN 25-30, 2011 -- Torino, ITALY
Keywords: Theileria parva; East Coast fever; antitheilerial; enolase; inhibitor design